Development Of Landmark Signage Design for Semarang City “Sebaru (Semarang Hebat Baru)” Using Atumics Method - Erisa Adyati Rahmasari; Dzuha Hening Yanuarsari; Agus Setiawan (Texture : Art And Culture Journal, 2025)
Semarang city landmark is one of the symbols of the city which can be in the form of a building which is one of the unique characteristics of the city of Semarang. Landmarks can be in the form of architectural buildings that are distinctive and able to provide aesthetics of space and good views of the city. Landmarks can also be used to attract the interest of tourists visiting the city. The results of observations and questionnaire studies that have been carried out by researchers at this time show that the landmarks of the city of Semarang do not really show the characteristics of the city of Semarang. Architectural buildings and arts in the city of Semarang became the inspiration for the development of landmark designs in the city of Semarang. The purpose of this design is to develop an existing landmark signage design based on the results of research and research conducted. The method for analysis in this design uses the ATUMICS method. The output or final result in the development of this landmark signage design is used as a reference material in the development of landmark signage designs in Semarang City. The benefits of this design are as a development of the characteristics of the city of Semarang as well as a support in the development of tourism in the city of Semarang.